Growth and Yield of Four Varieties of Soybean Plants Against the Application of Various Doses of Oil Palm Empty Bunch Fertilizer - Kinata, Andreani; Susanti, Yensi Melya; Parwito, Parwito (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
Soybeans are on the list of essential food crops after rice and corn. Soybean seeds contain nutrients, including protein, which is the primary protein source for most people in Indonesia. Increased production in intensification is achieved by utilizing varieties and improving planting media. One of the planting media improvements is using oil palm empty fruit bunches. The research was conducted from April to July 2022 at the experimental field of the Faculty of Agriculture, Ratu Samban University, Arga Makmur, North Bengkulu Regency, Bengkulu Province, Indonesia.Â The research used a randomized complete group design with two factors. The first factor was soybean varieties, consisting of V1 = Detam 1, V2 = Detam 4, V3 = Devatra 1, and V4 = Devatra 2. The second factor was the dose of oil palm empty fruit bunch compost. The levels were T1 = 20 tons per ha, T2 = 15 tons per ha, T3 = 30 tons per ha, and T4 = 40 tons per ha. The results showed that the Devatra 1 variety was the best, especially during the vegetative phase, while the generative phase was Detam 1. The higher the dose of oil palm empty fruit bunch compost fertilizer, the better in improving the growth and development of soybean plants. There is no interaction between the treatment of varieties and the dose of oil palm empty fruit bunch compost.